Epistemologi Tafsir Ayat-ayat Jihad: Studi Pemikiran Muhammad Chirzin dan Sahiron Syamsuddin - Tomi Liansi; M. Zia Al-Ayyubi (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2022)
Jihad in the recent decade has become a sensitive issue due to misconceptions rooted in a literal understanding that associates jihad with religious violence, an idea that is frequently referred to as 'holy terrorism.' In reality, jihad has a broader meaning that is not synonymous with violence or war. This study discusses the interpretations of two important figures in Qur'anic and Tafsir scholarship in Indonesia today, namely Muhammad Chirzin and Sahiron Syamsuddin, in order to reveal the meaning of jihad and examine the construction of thought that underpins that meaning, particularly in the Indonesian context. The question that will be studied by this paper is how the thoughts of the two figures in interpreting the verses of jihad and how the epistemological structure of the interpretation of the verses of jihad of the two figures? To answer these questions, this article uses a historical-factual approach. This paper contends that the two figures discussed have conducted extensive research on the concept of jihad, and the results of their interpretations disprove the identical association between jihad and war. According to Muhammad Chirzin, the object of jihad is all forms of evil, so jihad for him takes two forms: policy socialization and internalization (amar makruf) and prevention and elimination of evil (nahi munkar). Meanwhile, Sahiron Syamsuddin defines jihad as the removal of oppression, the preservation of religious freedom, and the establishment of peace. These two figures demonstrate that jihad, when studied thoroughly using valid academic instruments, does not justify violence and terrorism.